2007
DOI: 10.1097/01.jto.0000283408.85001.f3
|View full text |Cite
|
Sign up to set email alerts
|

PD3-2-6: Interim safety results from the East/South East (E/SE) Asian subgroup of the open-label TRUST (TaRceva lUng cancer Survival Treatment) study of erlotinib for advanced non-small-cell lung cancer (NSCLC)

Abstract: S464to the extremes of ranges, and start date for length of survival: method 1. progression after second line therapy or three weeks post last dose of chemo for control group and start date of erlotinib for treatment group; method 2. last date of second line therapy for both groups. 75 control and 70 erlotinib patients were included in the analysis. Results are presented in the table. The Incremental Cost-Effectiveness Ratio (ICER) was $28,516 per life-year-gained under method 1, and $17,632 under method 2. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Interim safety data from TRUST confirm the favorable safety profile of erlotinib observed in the BR.21 trial, and preliminary efficacy data are promising (disease control rate 68% and median PFS 13 weeks) [63]. Analyses of the European [64] and East/South East Asian subgroups [65] of the TRUST trial also support the safety profile observed for erlotinib in previous trials.…”
Section: Erlotinib In Second-line Nsclcsupporting
confidence: 63%
“…Interim safety data from TRUST confirm the favorable safety profile of erlotinib observed in the BR.21 trial, and preliminary efficacy data are promising (disease control rate 68% and median PFS 13 weeks) [63]. Analyses of the European [64] and East/South East Asian subgroups [65] of the TRUST trial also support the safety profile observed for erlotinib in previous trials.…”
Section: Erlotinib In Second-line Nsclcsupporting
confidence: 63%